2016
DOI: 10.1186/s12902-016-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of tolvaptan for the treatment of hyponatraemia secondary to syndrome of inappropriate antidiuretic hormone secretion in Sweden

Abstract: BackgroundTolvaptan is the only vasopressin V2 receptor antagonist licensed by the European Medicines Agency for the treatment of hyponatraemia (HN) secondary to the syndrome of inappropriate antidiuretic hormone secretion (SIADH). We have investigated the cost-effectiveness of tolvaptan versus no active treatment (NAT) in adult patients within the licensed indication who have either failed to respond to fluid restriction or for whom the use of fluid restriction is not suitable, from the societal perspective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
0
16
0
1
Order By: Relevance
“…These studies reported effective correction of hyponatremia and improvement of performance status, without any serious adverse events. However, according to our systematic search, in lung cancer patients, the effect of V2R antagonist treatment on mortality has only been evaluated in one study, which also demonstrated the cost-effectiveness of tolvaptan treatment in Swedish patients with SIADH in pneumonia or SCLC [72].…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported effective correction of hyponatremia and improvement of performance status, without any serious adverse events. However, according to our systematic search, in lung cancer patients, the effect of V2R antagonist treatment on mortality has only been evaluated in one study, which also demonstrated the cost-effectiveness of tolvaptan treatment in Swedish patients with SIADH in pneumonia or SCLC [72].…”
Section: Discussionmentioning
confidence: 99%
“…UADHS gelişmiş KHAK vakalarında, tedavi sonrası serum sodyum takibi rekürrensi saptamada kullanılabilmektedir. Tolvaptan vazopressin V2 antagonistidir (75) . Yalnızca oral olarak kullanılır ve günlük doz 15 mg'dır.…”
Section: Tanıunclassified
“…Jamookeeah et al ( 65 ) performed a cost-utility analysis using a discrete event simulation to model the progression of patients with hyponatremia due to SIADH who have failed fluid restriction (or were not suitable to fluid restriction) and were therefore treated with tolvaptan or no active treatment through inpatient admissions over a 30-day period in Sweden. Tolvaptan use was associated with reduced costs and increased quality-adjusted life years compared with no active treatment strategy.…”
Section: Remaining Uncertainties About the Use Of Vras In Hyponatremimentioning
confidence: 99%